GAP rater certification program transforms the rater certification process: Human/Trial design. (7th December 2020) - Mohs, Richard; Smith, Katy; Bork, Jason; Bartolic, Edward I.; Jenkins, Cecily; Ward, Rick; Rentz, Dorene M.
Abstract: Background: Rater certification is a key component in successful study startup and Alzheimer's disease (AD) trial execution, but the current certification process is time consuming and redundant across trials. Existing rater training has not changed substantially in years, has become more complex, and offers raters limited opportunity to enhance cognitive assessment skills. Method: The GAP Rater Certification Program is designed to transform rater certification. The GAP‐Net Rater Certification Matrix defines scale‐specific standards for proven, experienced, and developing raters (Figure 1). Standards are based on education, experience, previous certification, and demonstration of mastery. Rater training and certification follow defined processes and include the option to recertify after one year (Figure 2). Training is appropriately targeted to the rater's level of experience and effectively tests the rater's knowledge of each cognitive assessment. Rater qualifications maintained in a single database eliminate the need to complete Rater Experience Surveys (RES) on every trial. Result: The GAP Rater Certification Program has been delivered to over 50 raters across 20 GAP‐Net sites. GAP is surveying participating raters and will share results of the Program's implementation and impact. Initial results indicate the following: GAP's Demonstration of Mastery provides effective 'applied training' by assessing rater's knowledge of scales and administration competency and also providing a platform to share strategies that deliver meaningful outcomes. A rater certification process across AD trials is highly likely to save time during the qualification process and accelerate study startup. Expanding the Program to new / developing raters will increase the pool of raters at sites and eliminate potential startup bottlenecks. The applied training is appropriately targeted to rater's level of experience. Redundant training will be minimized. One model predicts 84 hours would be saved using the Program over 6 trials for every site. GAP Rater Certification Database (InvestigatorSpace) facilitates information collection and sharing and increases efficiency during site selection and study startup. Conclusion: The GAP Rater Certification Program removes redundancies in study startup and incorporates targeted training and Demonstration of Mastery designed to ensure quality raters and study data. Further enhancements will continue to focus on improving efficiencies and precision in rater qualification.